Short-term Supplemental Dietary Potassium from Potato and Potassium Gluconate Effect on Potassium Retention in Pre-Hypertensive-to-Hypertensive Adults (P24-051-19). (13th June 2019) - Stone, Michael; Martin, Berdine; Cao, Sisi; Weaver, Connie
Abstract: Objectives: Potassium is an essential nutrient of concern according to recent Dietary Guidelines for Americans Advisory Committees. Current recommendations established by the Institute of Medicine (IOM) are given as an Adequate Intake (AI) of 4700 mg/d, met by less than 3% of the population. Little is known about potassium (K) tissue retention and less is understood on how retention may affect health outcomes. In this clinical trial, we assessed the effects of K intake from potato sources and a K supplement on overall K balance. Methods: Thirty pre-hypertensive-to-hypertensive (Systolic BP ≥ 120 mmHg) men ( N = 15) and women ( N = 15) with a mean ± SD age, BMI, and BP (systolic(SBP)/diastolic(DBP)) of 48.2 ± 15 y, 31.4 ± 6.1, and 136.3 ± 11.9/86.1 ± 7.1 mmHg, respectively, were enrolled in a cross-over randomized control diet trial. Participants were assigned to a random order of four 16-day dietary K interventions including a basal diet (control) of 2300 mg/d(∼60 mmol/d), and three periods of an additional 1000 mg/d(3300 mg/d(∼85 mmol/d) total) of K in the form of potatoes (baked, boiled, or pan-heated with no additional fat), French fries, or a K gluconate supplement. Each intervention period was separated by two or more weeks of wash out. Twenty-four hour urine and stool samples were collected throughout each intervention phase, and assessed via ICP-OES for K, sodium (Na), and calcium (Ca) content. Results for differences in mineral balance were assessed as % (%) of intake by 15-day sums as follows: retention = dietary intake – urine + stool losses. Results: Using a mixed model with repeated measures and follow-up contrast analyses, initial analysis shows no significant differences ( P > 0.05) in % mineral retention (± SE) for K (control: 28.92 ± 7.19, French fries: 30.37 ± 5.81, potatoes: 26.39 ± 5.11, supplement: 34.52 ± 6.53), Na (control: 23.42 ± 10.34, French fries: 30.37 ± 8.03, potatoes: 20.15 ± 6.86, supplement: 26.47 ± 10.14), or Ca (control: 25.21 ± 11.23, French fries: 16.61 ± 13.47, potatoes: 24.22 ± 4.56, supplement: 31.46 ± 8.22). Conclusions: Although there appears to be no difference in mineral retention due to source, these findings may challenge the current dogma that K and Na intake are equivalent to urinary output, and raise the question of how retention in various tissues can influence health outcomes. Funding Sources: The Alliance for Potato Research and Education.